Integrating Physical and Non-Physical Work Environment to Enhance Employee Productivity: An Ergonomics and JD–R-Based Study at the Moro’o Sub-District Office, West Nias - Yoel Tatema Hia; Odaligoziduhu Halawa; Maria Magdalena Bate'e (Research Synergy Foundation, 2025)
The work environment plays an important role in determining employee productivity, especially in the public sector which is oriented towards community service. A conducive work environment—both physically and non-physically—can increase enthusiasm, concentration, and performance, while unsupportive conditions have the potential to reduce productivity and increase stress. This study aims to: (1) describe the working environment conditions at the Moro’o Subdistrict Office in West Nias Regency, (2) identify factors that affect employee productivity, and (3) analyse the relationship between the physical and non-physical working environment and employee productivity. The study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the physical work environment still faced several obstacles, particularly related to uneven lighting, suboptimal air quality and ventilation, cramped and disorderly room layout, and noise during busy service hours. In contrast, the non-physical work environment is relatively strong, characterised by supportive leader-subordinate relationships, open communication, and harmonious cooperation among colleagues. The interaction between physical limitations and non-physical strengths simultaneously affects the comfort, efficiency, and productivity of employees in providing services to the community